ETHANOL-INDUCED ALTERATIONS IN CARDIAC ENZYMES–AMELIORATIVE EFFECT OF THESPESIA POPULNEA LEAF EXTRACT - Rajbanshi, Sangeetha L. A.; Paranjape, Archana N.; Appanna, Vasu (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study covers the estimation of changes in cardiac enzymes such as ATPases and antioxidant enzymes following ethanol-administration in rats, and the possible ameliorative effect of leaf extract of the plant Thespesia populnea (TP) on these changes. Methods: Male adult Wistar rats were divided into 10 groups of six rats each. Vehicle controls received 5% gum acacia. Experimental groups received ethanol (20%, 2g/kg); or TP leaf extract (200 mg/kg and 400 mg/kg respectively); or vitamin E (25 mg/kg); or carvedilol (1 mg/kg) per orally every morning for 6 w, individually as well as in combination with ethanol. Following this, changes in the activities of Na+ ATPase, Ca2+ATPase, Mg2+ATPase, and antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) were determined in the heart tissue and compared with those in vehicle control. Results: Ethanol (20%, 2g/kg) treatment caused a reduction from the vehicle control in activities of all the examined enzymes, with minimal reduction in Mg2+ ATPase activity (29.26%) and maximal reduction in CAT activity (71.05%). With TP leaf extracts of 200 and 400 mg/kg, vitamin E and carvedilol individually, the vehicle controls showed percent changes in enzyme activities ranging from â€’8.24% for Mg2+ ATPase activity to+109.39% for Na+ ATPase activity caused by carvedilol. When administered along with ethanol, TP leaf extracts, vitamin E and carvedilol reversed the effect of ethanol to various degrees and brought back the enzyme activities to near vehicle control levels. While recovery with 200 mg Thespesia leaf extract was less, ranging from 24.1% for Mg2+ATPase activity to 190.91% for CAT activity, 400 mg Thespesia extract effected a greater recovery, with a minimum of 48.19% for Mg2+ ATPase activity and a maximum of 222.73% for CAT activity, as compared with ethanol-treated rats as controls. These effects could be interpreted in terms of the adverse effects of ethanol on cardiac function and the ameliorative effects, primarily the antioxidant potential, of TP leaf extracts, vitamin E and carvedilol. Conclusion: The restoration of enzyme activities with TP leaf extract may promote recovery of cardiac tissue from oxidative damage. Results from the current study indicate that treatment with TP leaf extract reduces ethanol-induced oxidative stress in rat heart and hence may help prevent cardiac damage. Â